2020
DOI: 10.14295/bds.2021.v24i1.2112
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gingival Hyperplasia Induced by Anticonvulsants: A Systematic Review

Abstract: Objective: Gingival hyperplasia (GH) is one of the side effects of anticonvulsant drugs. The aim of this study was to verify the prevalence of GH associated with the use of anticonvulsant, through a systematic review. Material and Methods: Systematic search was done at databases Pubmed and Embase between January 1984 and March of 2020 for identification of articles addressing the prevalence of GH associated with the use of anticonvulsant drugs. The methodological index for non-randomized studies (MINORS) was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…One year after starting the use of phenytoin, the first article considering gingival enlargement as an adverse effect of the use of this class of medication was published (Kimball, 1939). On the other hand, in a systematic review, the authors concluded that phenytoin is the drug that causes the highest prevalence of GH in patients who use it (Cláudio, et al, 2021). The pathogenesis of this condition depends on several factors, including the quality of plaque control, gingival inflammation, age, sex, duration of therapy, concentration of drug used, concomitant use of some medications, and genetic factors (Nakib, et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One year after starting the use of phenytoin, the first article considering gingival enlargement as an adverse effect of the use of this class of medication was published (Kimball, 1939). On the other hand, in a systematic review, the authors concluded that phenytoin is the drug that causes the highest prevalence of GH in patients who use it (Cláudio, et al, 2021). The pathogenesis of this condition depends on several factors, including the quality of plaque control, gingival inflammation, age, sex, duration of therapy, concentration of drug used, concomitant use of some medications, and genetic factors (Nakib, et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that phenytoin used for the treatment of epilepsy induced gingival growth in about 50% of patients (Tan, et al, 2004), although some patients did not present excessive gingival growth. Nevertheless, some authors have reported that the occurrence of GH caused by phenytoin is 40 to 50% (Kimball, 1939;Annegers, 1997;Cláudio, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Adjunctive mood stabilizer (i.e., lithium) and anticonvulsant (i.e., sodium valproate) agents could be used [ 35 , 36 ]. Adjunctive mood stabilizer agents affect negatively maintaining oral health care as they produce xerostomia and gingival enlargement, which increase the risk of dental caries and complicate maintaining good oral hygiene [ 37 ].…”
Section: Reviewmentioning
confidence: 99%